Peningkatan Kemampuan Guru dalam Penulisan Karya Ilmiah Melalui Pelatihan Penulisan Laporan Best Practice - Sophia Tri Satyawati; Yari Dwikurnaningsih; Bambang Ismanto; Mawardi; Endang Shobariyah; Retno Pramasari; Elsa K.Filimdity; Nicolas Bagas Dwi Kurniadi; Fery Virgiawan Tampatonda; Yohanes Dewa Aji Pangestu (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the ability of teachers to write best practice scientific papers. The training participants consisted of 30 teachers from public elementary schools in Banyubiru District, Semarang Regency. The training was held on August 8, 15, and 22, 2024, including the following stages; 1) Planning, 2) Implementation, and 3) Evaluation. The success of writing best practice scientific papers out of 30 participants there were 5 (16.67%) participants with very good categories, 18 (60.00%) participants with good categories, 4 (13.33)%) participants with poor categories, and 3 (10%) participants with poor categories. Overall, there were 23 (76.67%) participants who successfully compiled scientific papers. The evaluation results showed: 1) Evaluation of reaction, participant satisfaction is very high (89, 81); 2) Evaluation of learning, students' knowledge increased from a score of 61.33 before training to a score of 79.00 after training; 3) Behavior evaluation, there is a change in behavior with a high score (80.00); 4) Result evaluation, the results of the training have a high impact (83.88) on teacher professionalism, learner achievement and school quality.